Effects of ewes grazing sulla or ryegrass pasture for different daily durations on forage intake, milk production and fatty acid composition of cheese. (22nd June 2016) - Bonanno, A.; Di Grigoli, A.; Mazza, F.; De Pasquale, C.; Giosuè, C.; Vitale, F.; Alabiso, M.
Abstract : Sulla ( Sulla coronarium L.) forage is valued for its positive impact on ruminant production, in part due to its moderate content of condensed tannin (CT). The duration of daily grazing is a factor affecting the feed intake and milk production of ewes. In this study, the effects of grazing sulla pasture compared with annual ryegrass, and the extension of grazing from 8 to 22 h/day, were evaluated with regard to ewe forage intake and milk production, as well as the physicochemical properties and fatty acid (FA) composition of cheese. During 42 days in the spring, 28 ewes of the Comisana breed were divided into four groups (S8, S22, R8 and R22) that grazed sulla (S) or ryegrass (R) for 8 (0800 to 1600 h) or 22 h/day, and received no feeding supplement. In six cheese-making sessions, cheeses were manufactured from the 48 h bulk milk of each group. Compared with ewes grazing ryegrass, those grazing sulla had higher dry matter (DM) intake, intake rate and milk yield, and produced milk that was lower in fat and higher in casein. Ewes grazing for 22 h spent more time eating, which reduced the intake rate, increased DM and nutrient intake and milk yield, and reduced milk fat. Due to the ability of CT to inhibit the complete ruminal biohydrogenation of polyunsaturated fatty acids (PUFA), the FA composition of sulla cheese was more beneficial for consumer health compared with ryegrass cheese, having lower levels of saturated fatty acids and higher levels of PUFA and n-3 FA. The FA profile of S8 cheese was better than that of S22 cheese, as it was higher in branched-chain FA, monounsaturated FA, PUFA, rumenic acid ( c 9, t 11-C18:2), and had a greater health-promoting index. The effect of short grazing time on sulla was attributed to major inhibition of PUFA biohydrogenating ruminal bacteria, presumably stimulated by the higher accumulation of sulla CT in the rumen, which is related to a higher intake rate over a shorter eating time. Thus, grazing sulla improved the performance of ewes, thereby increasing, especially with short grazing time, the nutritional properties of cheese fat.